Arabic and its alternatives : religious minorities and their languages in the emerging nation states of the Middle East (1920-1950) - Baarda, Tijmen C.; Murre-van den Berg, H. L. 1964-; Sanchez-Summerer, Karene (Christians and Jews in Muslim Societies, 2020)
"Arabic and its Alternatives discusses the complicated relationships between language, religion and communal identities in the Middle East in the period following the First World War. This volume takes its starting point in the non-Arabic and non-Muslim communities, tracing their linguistic and literary practices as part of a number of interlinked processes, including that of religious modernization, of new types of communal identity politics and of socio-political engagement with the emerging nation states and their accompanying nationalisms. These twentieth-century developments are firmly rooted in literary and linguistic practices of the Ottoman period, but take new turns under influence of colonization and decolonization, showing the versatility and resilience as much as the vulnerability of these linguistic and religious minorities in the region. Contributors are Tijmen C. Baarda, Leyla Dakhli, Sasha R. Goldstein-Sabbah, Liora R. Halperin, Robert Isaf, Michiel Leezenberg, Merav Mack, Heleen Murre-van den Berg, Konstantinos Papastathis, Franck Salameh, Cyrus Schayegh, Emmanuel Szurek, Peter Wien".